O gosto pela ciência e pelas aulas de ciências: estudo envolvendo os anos finais do ensino fundamental - Pacheco, Julia Nunes (2022)
The present study starts from the premise that the affective dimension, understood as linked to issues of commitment, emotion and motivation, has an influence on the quality of learning and, therefore, constitutes an aspect of relevance in terms of science teaching. The problem lies in the fact that, although this dimension proves to be influential in learning, it is often not considered by teachers. The study dialogues, therefore, with the affective dimension through the voice of students and teachers in relation to the Science curricular component. To this end, the following research questions are structured: What are the feelings that elementary school students have in relation to science and science classes? How do teachers consider the affective dimension as an integral part of their pedagogical actions? To answer them, the research is structured in two empirical studies, in addition to a broad review of research published in the Web of Science database, regarding the theme affectivity and science teaching. The first empirical study is associated with the application of a questionnaire developed by a team of researchers from Spain, Chile and Brazil and which is being applied in different countries. In the context of this dissertation, the questionnaire was restricted to a group of 350 elementary school students in the final years of two Brazilian state public schools. The second empirical study is linked to interviews carried out with ten Science teachers who work from the sixth to the ninth year of Elementary School – Final Years in Brazil. The results of the application of the questionnaire on the feelings of students in Elementary School - Final Years, in relation to science and science teaching - point to the presence of some elements that integrate the affective dimension of the study, with emphasis on the presence of commitment to studying science, extrinsic motivation and the absence of emotions through the study of this curricular component or even through science itself. Regarding the speech of the teachers who teach Science classes, it is observed that it is possible to identify a convergence regarding the importance for the teaching of Science. However, some teachers conceive the affective dimension as a relationship of affection between teacher and student, while others perceive it in motivation, emotions, self-esteem, self-efficacy, among other factors, following what was considered in the present study. In addition, the teachers interviewed point to the most exciting moment in Science classes when students carry out experimental activities.